Immediate and Short-Term Effects of Short- and Long-Duration Isometric Contractions in Patellar Tendinopathy. Issue 4 (July 2020) - Pearson, Stephen J.; Stadler, Sarah; Menz, Hylton; Morrissey, Dylan; Scott, Isabelle; Munteanu, Shannon; Malliaras, Peter
Abstract : Objectives: Isometric muscle contractions are used in the management of patellar tendinopathy to manage pain and improve function. Little is known about whether long- or short-duration contractions are optimal to improve pain. This study examined the immediate and short-term (4 weeks) effects of long- and short-duration isometric contraction on patellar tendon pain, and tendon adaptation. Design: Repeated measures within groups. Setting: Clinical primary care. Patients: Participants (n = 16, males) with patellar tendinopathy. Intervention: Short-duration (24 sets of 10 seconds) or long-duration (6 sets of 40 seconds) isometric knee extension loading (85% maximal voluntary contraction), for 4 weeks. Main Outcome Measure: Immediate change in pain with single-leg decline squat (SLDS) and hop, as well as change in pain and tendon adaptation [within-session anterior–posterior (AP) strain] were assessed over 4 weeks. Results: Pain was significantly reduced after isometric loading on both SLDS ( P < 0.01) and hop tests ( P < 0.01). Pain and quadriceps function improved over the 4 weeks ( P < 0.05). There was significant AP strain at each measurement occasion ( P < 0.01). Although transverse strain increased across the training period from ∼14% to 22%, this was not significant ( P = 0.08). Conclusions: This is the first study to show that short-duration isometric contractions are as effective as longer duration contractions for relieving patellar tendon pain when total time under tension is equalized. This finding provides clinicians with greater options in prescription of isometric loading and may be particularly useful among patients who do not tolerate longer duration contractions. The trend for tendon adaptation over the short 4-week study period warrants further investigation.